ANALYSIS OF SELF-DEFENCE A STATEACCORDING TOINTERNATIONAL LAW - Adelia Putri Zulkarnain; Lina Hastuti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Self-defence in international law is an inherent right of the state to defend its sovereignty and territory from armed attacks conducted by other countries against it. However, Self-defence is often used by countries to compete for strength and initiate attacks. This study is examining the various provisions governing the application of Self-defence which are justified under International Law. This type of study is normative legal research. The problem approach used was the statute approach, conceptual approach, and case approach. The results of the study explained that Self-defence is the right of every country to use violence in the event that its sovereignty is threatened and endangering international security and peace. The provisions of international law make it clear that the right to defend or self-defence the main country must have received an attack or an imminent threat from another country and this attack was conducted by military forces.